THE CLASSICAL GUITAR IN THE MIRROR OF THE RUSSIAN MUSICAL HISTORIOGRAPHY - AGAFITA, MIHAIL (Notograf Prim, 2021)
The article is dedicated to Russian scientific sources about the modern classical guitar written by A. Petropavlovsky, V. Ganeev, K. Ilyghin, D. Krutikov. In A. Petropavlovsky’s work “Guitar in the Chamber Ensemble” three stages of the participation of the guitar within the instrumental ensemble are revealed. On this basis, the author of this article completes the classification of the Russian scientist, adding the genre of concerto for guitar and orchestra. V. Ganeev’s work “Classical Guitar in Russia: the Problem of Academic Status” deals with ideological obstacles that caused the lack of support for the instrument from the music education system. In D. Krutikov’s research entitled “The Art of Guitar in Petersburg-Petrograd-Leningrad in the First Half of the 20th Century”, are studied the influences of European and American musicians on the formation of guitar interpretation and teaching school in the Russian cultural capital. The explored sources occupy an important place in Russian historiography, providing the researchers of the modern classical guitar with an advanced methodology